Pengaruh Dosis Pupuk NPK (15:15:15) Terhadap Pertumbuhan dan Hasil Tanaman Padi Sawah (Oryza Sativa L.) Dengan Metode Sri (System Of Rice Intensification) - Kevin Hijrah Saputra; Bustari Badal; Syamsuwirman (Jurnal Research Ilmu Pertanian, 2022)
Research on the effect of dosage of NPK fertilizer on the growth and yield of Paddy Rice (Oryza sativa L.) Using the SRI (Sytem of Rice Intensification) Method in Korong Kapalo Banda, Nagari Aie Tajun District, Padang Pariaman Regency, from January to April 2021. This study aims to obtain the best dose of NPK fertilizer to support the growth and yield of lowland rice using the sri method. This study used a randomized  block design (RAK)with 5 treatments and 4 groups in the form of a plot. The data for each observation obtained were analyzed by means of variance, and continued with Duncan’s New Mutiple Range Test( DNMRT) further test at the 5% level. From the experiments that have been carried out, several conclusions can be drawn: the application of N, P, K fertilizer with the SRI method has a very significantly different effect the prameters of plants height, average grain number of panicles, 1000 seed grain weight, and grain weight yield. Per plot bad had no significant effect the percentage of productive tillers. The N4 treatment was the best dose and increased the growth yield of rice plants. It is tecommended to use N4 treatment (200 kg ha-1) on rice plants using the System of Rice Intensification method to get the best.